Phosphorus requirements of grow-finish pigs raised in a commercial environment - C W Hastad; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
We conducted three experiments to identify available phosphorus (aP) requirements of pigs reared in commercial facilities. In a pilot study (Exp. 1), 600 gilts (PIC, initially 95.2 lb) were randomly allotted to a low or high dietary P regimen in a 98-d study. Pigs were phase-fed six diets from 95 to 106, 106 to 150, 150 to 183, 183 to 212, 212 to 245, and 245 to 267 lb. Corresponding aP concentrations were: 0.30, 0.28, 0.27, 0.27, 0.24, and 0.19% (low) and 0.37, 0.33, 0.30, 0.28, 0.27, and 0.26% (high). No differences were observed (P>0.10) in ADG and overall F/G was greater (P<0.07) for pigs fed the low aP regimen. In Exp. 2, 1,260 gilts (initially 74.5 lb) were randomly allotted to one of five dietary treatments in a 26-d study. Experimental diets contained 0.18, 0.22, 0.25, 0.29, or 0.32% aP, corresponding to 0.5, 0.6, 0.7, 0.8, or 0.9 g aP/Mcal ME. There were 28 pigs per pen and 9 pens per treatment. From d 0 to 14, increasing aP tended to increase (linear, P<0.03) ADG and F/G (quadratic, P<0.05) with the greatest response observed as aP increased from 0.18 to 0.22%. However, from d 0 to 26, no differences were observed for any growth traits (P>0.12). Pooled bending moment of the femur, 6th rib, and 3rd and 4th metatarsals increased with increasing aP (linear, P<0.01). Ash content of the rib and metatarsals numerically increased (P>0.10) with increasing aP. In Exp. 3, 1,236 gilts (initially 195.1 lb) were randomly allotted to one of five dietary treatments in a 28-d study. Experimental diets contained 0.05, 0.10, 0.14, 0.19, 0.23% aP, equivalent to 0.152, 0.277, 0.402, 0.527, or 0.652 g aP/Mcal ME. From d 0 to 14, increasing aP increased (linear, P<0.01) ADG and F/G. However, from d 0 to 28 increasing aP had no effect (P>0.17) on growth performance. Increasing aP increased (linear, P<0.05) bone ash and bending moment of the 3rd and 4th metacarpals. In commercial facilities, 74 to 121 lb pigs require approximately 0.22% aP to maximize ADG and F/G, whereas 195 to 240 lb pigs require approximately 0.19% aP. However, bone bending moment and ash continued to increase with increasing aP. These values correspond to 0.60 and 0.527 g aP/Mcal ME and 3.24 and 4.07 g/d of aP intake. Our results suggest percentage aP requirement estimates are similar to NRC (1998); however, because of the low feed intake of pigs in commercial facilities our study shows a lower requirement estimate on a g/d basis.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Grow-finish pigs; Phosphorus; Growth Performance; Swine